The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpsyg.2022.883833
|View full text |Cite
|
Sign up to set email alerts
|

Functional Impairment in Borderline Personality Disorder: The Mediating Role of Perceived Social Support

Abstract: Borderline personality disorder (BPD) is characterized by instability in relationships, mood fluctuations, and erratic behavior. This study investigates the relationship between pathological personality traits and functional disability, the status of perceived social support in BPD, as well as its mediating role in this relationship. In this cross-sectional study, 192 Spanish women (BPD group, N = 97; healthy control group, N = 95) completed, through two online platforms, a battery of tests including: the Pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The role of perceived social support as a mediator in the relationship between stress and depression has been widely studied amongst a variety of stressors [ 45 , 46 , 47 , 48 ] and in a variety of populations. For example, postpartum women [ 49 ], women with breast cancer [ 50 ], university graduates [ 51 ], and pregnant women [ 52 ] have all confirmed that perceived social support mediates the relationship between perceived stress and depression.…”
Section: Introductionmentioning
confidence: 99%
“…The role of perceived social support as a mediator in the relationship between stress and depression has been widely studied amongst a variety of stressors [ 45 , 46 , 47 , 48 ] and in a variety of populations. For example, postpartum women [ 49 ], women with breast cancer [ 50 ], university graduates [ 51 ], and pregnant women [ 52 ] have all confirmed that perceived social support mediates the relationship between perceived stress and depression.…”
Section: Introductionmentioning
confidence: 99%